Reducing Anxiety of Pregnant Women with a History of Pregnancy Loss-A Randomize Clinical Trial - Zaraj, Hoda; Vakilian, Katayon; Rezveh, Fatemeh M. (Current Women's Health Reviews, 2020)
Background: Spontaneous abortion is the most common complication of pregnancy which is considered an unfavorable experience both physically and psychologically. Objective: This study was conducted to investigate the effect of group counseling through cognitive behavioral therapy (CBT) on the anxiety of pregnant women with a history of spontaneous abortion. Methods: This study was randomized clinical trial type, in which convenient sampling was performed to select 64 subjects from healthcare centers in Arak province. After receiving written consent from the participants, the sampling was performed and the subjects were categorized randomly into two 32-subject groups as intervention and control. The intervention was performed as six 60- min sessions through cognitive behavioral therapy (CBT). Control group, however, only routine cares of pregnancy were provided. For data collection, The Spielberger State-Trait Anxiety Inventory was utilized at the beginning and end of the study. Then, the collected information was analyzed by SPSS 21 through paired t-test, independent t-test. Results: The mean anxiety after the intervention in the intervention and control groups was 65.13±8.11 and 75.91±5.56, respectively, whereby a significant difference was observed between the two groups (p≤0.05). Conclusion: It seems that women with a previous history of abortion require psychological support during pregnancy. It is recommended that the skills of midwives also be improved to psychologically support these women.
Keywords: cognitive behavioral therapy